2016
DOI: 10.1136/rmdopen-2015-000184
|View full text |Cite
|
Sign up to set email alerts
|

Patient-initiated appointments compared with standard outpatient care for rheumatoid arthritis: a randomised controlled trial

Abstract: ObjectivesTo test the hypothesis that implementing a patient-initiated system of care could improve clinical outcome in rheumatoid arthritis (RA) using disease activity guided management.MethodsAn 18-month controlled blinded end point two-centre study with 131 patients with RA randomised to intervention (n=64) or control (n=67). The intervention group participants were guaranteed appointments to a rheumatologist within 10 working days if they subjectively experienced a flare in disease activity. The control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
12
1
2
Order By: Relevance
“…In settings such as forestry and fishing, she showed that coproduction led to lower costs because it was a more efficient way to meet social and community needs. 21 Similar efficiencies are reported when coproduction is implemented in healthcare settings such as serious illness, 20 palliative care, 22 mental health, 23 rheumatology 24 and primary care. 25 Efficiency is particularly true where patients learn to self-manage complex processes such as dialysis (box 2), and for example parents who learnt how to do intravenous therapy at home for infection in cystic fibrosis saved an estimated 2000 hospital days per year at the Karolinska Institute (Andreas Hagar, 2018, personal communication).…”
Section: Economic Efficiencymentioning
confidence: 68%
See 1 more Smart Citation
“…In settings such as forestry and fishing, she showed that coproduction led to lower costs because it was a more efficient way to meet social and community needs. 21 Similar efficiencies are reported when coproduction is implemented in healthcare settings such as serious illness, 20 palliative care, 22 mental health, 23 rheumatology 24 and primary care. 25 Efficiency is particularly true where patients learn to self-manage complex processes such as dialysis (box 2), and for example parents who learnt how to do intravenous therapy at home for infection in cystic fibrosis saved an estimated 2000 hospital days per year at the Karolinska Institute (Andreas Hagar, 2018, personal communication).…”
Section: Economic Efficiencymentioning
confidence: 68%
“…The vertical line indicates when all rheumatologists in Gävle County used the coproduction dashboards, and demonstrates a clear additional improvement. 24 …”
mentioning
confidence: 99%
“…Secondly, he developed a new delivery model that they call an "open-tight" system. 24 In effect, patients were encouraged to use the dashboards at home to track outcomes and determine if they were in remission. If they were doing well, they were "open" to visit their physicians but making a visit was up to them.…”
Section: Discussionmentioning
confidence: 99%
“…PIFU with nurse involvement is found to be comparable to or better than traditional medical routine consultation, measured on both clinical and psychological factors [17][18][19]. Likewise, security was maintained with same level of decreased disease activity in PIFU guided by tight control of disease activity without affecting patient satisfaction, even among newly diagnosed patients, compared to traditional outpatient consultation every 3-4 months [21].…”
Section: Introductionmentioning
confidence: 77%